The success paradox : why we need a holistic theory of social mobility - Atherton, Graeme (Bristol : Policy Press, 2016)
This timely book provides an alternative vision of social mobility and a route-map to achieving it. It examines how the term 'social mobility' structures what success means and the impact that has on society. It recasts the relationship with employers and covers progress in non-work areas of life.
Title from publisher's bibliographic system (viewed on 01 Sep 2022).
Keywords: Social mobility; Education, Higher -- Social aspects